Determining the excited‐state substituent constants of furyl and thienyl groups. (9th January 2018) - Qu, Junyan; Cao, Chao‐Tun; Cao, Chenzhong
Abstract: Six series of styrene derivatives XCH═CHArY (total of 65) containing the styrene parent molecular skeleton were synthesized (here, Y is OMe, Me, H, F, Cl, CF3, CN, and NO2, and X is 2‐furyl, 3‐furyl, 2′‐methyl‐2‐furyl, 2‐thienyl, 3‐thienyl, and 2′‐methyl‐2‐theniyl). Their ultraviolet absorption spectra were measured in anhydrous ethanol, and their wavelength of absorption maximum λmax was recorded. For the wavenumber ν max (cm −1, ν max  = 1/λmax ) of the obtained λmax, a quantitative correlation analysis was performed, and 6 excited‐state substituent constants σ CC p ex of groups X were obtained by means of curve‐fitting method. Taking the ν max values of total 90 compounds of styrene derivatives as a data set (including 25 compounds from reference and 65 compounds of this work), a quantitative correlation analysis was performed, and the reliability of the obtained σ CC p ex was verified. In addition, 12 samples of disubstituted Schiff bases (XCH═NArY) involving the above groups X were synthesized, and their ν max values were recorded. Using these 12 ν max together with the 14 ν max values of Schiff bases taken from reference (total of 26 compounds), it was further verified that the σ CC p ex values are reliable by means of quantitative correlation method. Abstract : The excited‐state substituent constants σ CC p ex of 6 para‐furyl/thienyl groups were determined from 1‐furyl/thienyl‐2‐aryl ethylenes XCH═HArY. The results show that the effect of 2‐furyl/thienyl is greater than that of 3‐furyl/thienyl on UV absorption wavelength λmax of compounds, and the effect of 2‐furyl/thienyl makes the λmax of styrene derivatives and disubstituted Schiff bases red‐shift, comparing with the corresponding 3‐furyl/thienyl.